CALCULATION OF HEAT CAPACITY IN MEAT DURING ITS FREEZING CONSIDERING PHASE CHANGE - Yuriy M. Berezovskiy; Igor A. Korolev; Taras A. Sarantsev (Теория и практика переработки мяса)
As a consequence of insufficient study of water phase change in meat accompanied by water crystallization, its modeling is currently based on the empirical dependence of the frozen water portion on temperature. Such model does not allow answering a number of questions such as of metrological order, and also of physicochemical interpretation of processes occurring in meat during water crystallization. In this paper, we propose an approach to modeling the phase change process of meat during its freezing on the basis of the phonon theory of Debye crystallization, which allows to obtain physically justified dependences of heat capacity on temperature in the phase change region. The obtained dependences may serve as a simple method for calculating the heat capacity of meat in the temperature range of 113 K to the cryoscopic temperature of the given meat type, or as a basis for the analysis and correction of factors affecting the meat freezing in the temperature range of the phase change.